(3JMdjd fXQj hJWHjbjs - (3eUWai(B, (3WhjWjs ((3JdeSGf(B:s (3GdecJH GdLGeYj GdMOjK,s, 2017)
(3jVe eaGgje GdfXQjI GdEbJUGOjI, fXQjI GdWdH, fXQjI GdYQV, GdeQhfGJ, fXQjI JhGRf GdShb, fXQjI Sdhc GdeSJgdc GdcdGSjcjI(B"(3GdefaYI GdbjGSjI(B"(3, fXQjI Sdhc GdeSJgdc GdMOjKI(B"(3GGdefaYI GdJQJjHjI(B" (3eY HYV ef ehGVjY GeJMGf eNJGQI eY MdhdgG GdfehPLjIs
(3HHdjhZQGajG(B: (3U(B.355-356s
Keywords: (3GdEbJUGO GdLRFjs; (3GdEbJUGO(B-(3fXQjGJs